Incidencia jurídica del delito del femicidio y su aplicabilidad normativa en las unidades judiciales penales y tribunales penales del cantón Guayaquil en el período 2014 - León Paladines, Byron David (2015)
Nowadays you can see the radical change globally on the role of women in society. While it is true in the past the woman alone was considered useful for housework or some other work of little importance but in time now the woman has already been accepted and involved in different social aspects as well as political and economic. But although the woman has changed its role and importance in society there are still people who think they can have absolute control over them by taking them to commit crimes such as murder for wanting to control or simply because they are women……